KEPEMIMPINAN KELUARGA DALAM AL-QUR'AN (KAJIAN SURAT AL-NISA' [4]: 34) - Rokhman, Taufik (IAIN Pekalongan, 2013)
Abstract : The rijal word is a symbol of leadership (alqowwam) for nisa' . Rijal top leadership Nisa 'is based on the primacy (al-fadhalah) and financial support (nafaqah). The use of the word rijal and nisa' in this paragraph is semantically not emphasize the biological significance of the reference to sex, but the leadership of a person's character and social function. Semiotic elements in the lexicon rijal, qowwamun and the masculine pronoun hum ( هﻢ ) demonstrate leadership character (al-qawwam) is generally more dominant in the self-contained men from the women. It is by no means a necessity leadership of men over women in the family. Abstrak : Kata Rijal adalah simbol kepemimpinan (alqowwam) untuk nisa'. Rijal kepemimpinan atas Nisa 'didasarkan pada keutamaan (al-fadhalah) dan dukungan keuangan (nafaqah). Penggunaan kata Rijal dan nisa 'dalam ayat ini semantis tidak menekankan signifikansi biologis referensi seks, tapi kepemimpinan karakter seseorang dan fungsi sosial. Unsur semiotik dalam leksikon Rijal, qowwamun dan maskulin ganti hum (هﻢ) menunjukkan karakter kepemimpinan (al-qawwa m) umumnya lebih dominan pada laki-laki mandiri dari perempuan. Hal ini tidak berarti kepemimpinan kebutuhan lakilaki atas perempuan dalam keluarga.